A Multimodal Discourse Analysis of the Interpersonal Meaning of a Television Advertisement in Indonesia - Didin Nuruddin Hidayat; Abrizal A; Alek A (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
ABSTRACTThis article attempts to investigate and explore the interpersonal meaning of YOU C1000 on Indonesian television advertisements. This study was conducted qualitatively using case study to check how different semiotic and modes such as music, sound, speech, color, action, and image work together to build the interpersonal meaning. This study discusses the interpersonal meaning in speech and music, interpersonal meaning in movement and interpersonal meaning in image and color. The study aimed to give some contributions to social semiotics studies, television, or video advertisement. YOU C1000 advertisement is successful to attract audiences’ attention. The election of Miss Universe advertisement star, Bali as the shooting location, English as the language function and wedding ceremony as the activity are the significant factors to introduce the product to the market. In addition, its tagline is a successor factor as well. If people hear Healthy Inside and Fresh Outside, they will remember YOU C1000. ABSTRAKArtikel ini bertujuan untuk menginvestigasi and menyelidiki makna interpersonal dari produk ‘YOU C1000’ pada iklan televisi Indonesia. Penelitian ini dilakukan secara kualitatif dengan menggunakan pendekatan studi kasus untuk mengetahui bagaimana semiotik dan moda yang berbeda seperti musik, suara, ucapan, warna, tindakan, dan gambar, dapat berjalan bersama-sama dalam membentuk makna interpersonal. Penelitian ini mengulas makna interpersonal dalam ucapan dan musik, makna interpersonal dalam gerakan, dan makna interpersonal dalam gambar dan warna. Penelitian ini bertujuan untuk memberikan kontribusi pada studi semiotika sosial, televisi, atau iklan video. Iklan YOU C1000 berhasil menarik perhatian penonton. Pemilihan bintang iklan Miss Universe, Bali sebagai lokasi syuting, bahasa Inggris sebagai fungsi bahasa dan upacara pernikahan sebagai aktivitasnya adalah faktor-faktor yang signifikan untuk memperkenalkan produk tersebut ke pasar. Selain itu, ‘tagline’-nya juga merupakan faktor penting lainnya. Jika orang-orang mendengar ‘Healthy Inside and Fresh Outside’, mereka akan mengingat YOU C1000. How to Cite: Hidayat, D. N.., Abrizal., Alek. (2018). A Multimodal Discourse Analysis of the Interpersonal Meaning of a Television Advertisement in Indonesia. IJEE (Indonesian Journal of English Education), 5(2), 119-126. doi:10.15408/ijee.v5i2.11188